2018
DOI: 10.4236/oalib.1104336
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chitosan Membranes Crosslinked by Sulfuric Acid

Abstract: Development of novel biomaterials and its practical application have been the subject of much research in the field of scaffolds for tissue engineering, providing the success of producing scaffolds biomaterials that facilitate tissue growth and provide structure support for cells. Due to its biocompatibility and biodegradability, chitosan has been the focus of several researches in recent years to be applied in the biomedical field and chemical modifications of chitosan through crosslinks can produce materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…This corresponded to the previously reported pretreatment of biomass by the organosolv process, which led to high cellulose recovery in the solid fraction and more efficiency of hemicellulose and lignin solubilization compared to the other pretreatment methods . The structures of sheet materials observed was similar to those reported from previous works. According to previous SEM analysis, it was found that the paper sheets prepared from bleached BG and RG pulps presented the dense fiber with the short branch structure and long crisscross fiber, respectively . A fiber structure with small pores was shown from the paper-based bacterial cellulose–chitosan nanocomposites .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This corresponded to the previously reported pretreatment of biomass by the organosolv process, which led to high cellulose recovery in the solid fraction and more efficiency of hemicellulose and lignin solubilization compared to the other pretreatment methods . The structures of sheet materials observed was similar to those reported from previous works. According to previous SEM analysis, it was found that the paper sheets prepared from bleached BG and RG pulps presented the dense fiber with the short branch structure and long crisscross fiber, respectively . A fiber structure with small pores was shown from the paper-based bacterial cellulose–chitosan nanocomposites .…”
Section: Resultssupporting
confidence: 87%
“…42,49 The chitosan powder presented two different broad peaks at 2θ = 9.50 and 19.74°referred to the semicrystalline structure from strong intra-and intermolecular interactions of hydrogen bonds formed among amine, alcohol, and other functional groups present in the chitosan molecule. 30 In addition, the decrease in the intensity of the crystalline structure in the XRD pattern was related to the lower crystallinity index of all sheet materials with the range from 43.3 to 51.0% when compared to 65.7% of the commercial cellulose (Table 4). It indicated that the formation of hydrogen bonding between cellulose and chitosan led to the decline in the crystallinity index.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…XRD of cross-linked CS samples shows that the intensity of semicrystalline peaks of CS membrane further decreases with increased duration of cross-linking with sulphuric acid. This occurrence indicated that as the duration of chitosan's dissociation into the sulfuric acid increased, a high concentration of H + ions was produced, which then occupied the SO4 2− ions, thereby proving that the SO4 2− ions were incorporated with NH3 + groups to form ionic bridges between CS polymer chains [189,190]. Improved ionic conduction occurs preferably in the amorphous phase, in which cross-linking ensures the reduced crystallinity phase of CS [186,191].…”
Section: Chemical Cross-linkingmentioning
confidence: 98%
“…For the scaffold materials to be used as a supporting platform for cell growth and proliferation, it is important that they maintain their structure when in contact with an aqueous medium and that they have no cytotoxic effect due to the reagents used to create permanent and stable linkages between the polymer chains. 58,59 Recently, it has been shown that carboxylic acids can be used to cross-link biomaterials without compromising their cytocompatibility. 60 Citric acid is a metabolic product in the Krebs cycle and, therefore, an endogenous intermediate of the body, which makes it suitable for biomedical applications.…”
Section: Cytotoxicity Of Pva Electrospun Matsmentioning
confidence: 99%